درجة التوريث والتقدم الوراثي لبعض المؤشرات الإنتاجية والفسيولوجية في عدة طرز وراثية من القطن - خطاب محمد نائل; عبد العزيز محمد (Latakia University Journal -Biological Sciences Series, 2014)
استخدمت سبعة طرز وراثية من القطن وهي: (حلب133، حلب90، رقة5، دير الزور22، حلب118، حلب40، السلالة124) لدراسة الإنتاجية وبعض مكوناتها (متوسط وزن قطن الجوزة الواحدة(غ)، وزن 100 بذرة (غ)، معدل الحلج%،إنتاجية النبات الواحد /غ، كمية المادة الجافة/غ، إنتاجية وحدة المساحة كغ/هـ)، بالإضافة لبعض المؤشرات الفسيولوجية ( مساحة أوراق النبات/ سم2، دليل مساحة الأوراق%)، بتصميم القطاعات العشوائية الكاملة وبثلاثة مكررات، في سلحب بمنطقة الغاب – التابعة لمحافظة حماه في الموسم الزراعي 2012. تضمنت الدراسة تباين التراكيب الوراثية لمختلف الصفات المدروسة ودرجات التوريث العامة والتقدم الوراثي ومعامل الاختلاف ومعامل الارتباط لاستخدامها في برامج التربية. أظهرت الدراسة فروقات معنوية بين الطرز المدروسة لمعظم الصفات المختبرة. أشارت الدراسة إلى تفاوت قيم درجة التوريث والتقدم الوراثي من حيث الصفات الإنتاجية والفسيولوجية، فكانت أعلاها بالنسبة لدرجة التوريث إنتاجية القطن كغ/ هـ، مساحة أوراق النبات/ سم2، دليل مساحة الأوراق%، متوسط وزن قطن الجوزة الواحدة/ غ ( 0.99- 0.96- 0.97 – 0.93 على الترتيب) مترافقة مع تقدم وراثي ( 2.44- 8.23- 7.22- 4 % على الترتيب). كما أظهرت النتائج وجود ارتباط ايجابي ومعنوي بين إنتاجية القطن كغ/ هـ من جهة وبين كل من متوسط وزن قطن الجوزة الواحدة/ غ (r = 0.57**) ، ومع صفة إنتاجية النبات الواحد /غ r = 0.55**)) ومع كل من مساحة أوراق النبات الواحد/سم2 ودليل مساحة الأوراق%(r = 0.19)، ومع المادة الجافة% (r = 0.21)، وهذا يعطينا المجال وسهولة الحركة لوضع الأدلة الانتخابية العديدة من أجل تحسين القطن. Seven cotton varieties (Rakka 5, Aleppo133, Aleppo 90, Aleppo 118, Aleppo 40, Deir 22, and Line124) were used in the study of some quantitative characteristics of cotton yield and its components (seed cotton weight per boll/g, 100seed/g weight average, lint percentage %, seed cotton weight per plant/g, total dry matter weight, seed cotton yield per unit area kg/ha), and physiological qualities (leaf area cm2, leaf area index %). The seven varieties were grown in Salhab (Al-Ghab region, Hama) in 2012 using randomized complete block design with three replications. The study included estimating variance, broad sense heritability, genetic progress, and genetic correlation between cotton yield and its components, which is to be used in breeding programs. The study showed significant differences in the studied genotypes for most of the considered traits. The study also revealed a variation in the values of heritability, genetic advance in the productive and physiological characteristics, the highest heritability of which was in the seed cotton yield per unit area kg/ha, total leaf area cm2, leaf area index%, and seed cotton weight per boll/g, where the inheritance degree reached (0.99- 0.96- 0.97- 0.93). This was associated with a genetic development (2.44- 8.23- 7.22- 4). The results also showed a positive significant correlation between seed cotton yield per unit area and seed cotton weight per boll/g (r = 0.57**), seed cotton weight per plant/g (r = 0.55**), total leaf area cm2, leaf area index %, (r = 0.19), and dry matter weight (r = 0.21). This provides numerous pieces of evidence to improve cotton.